Sociodemographic and Pathological Characterization of Patients with Type 2 Diabetes Mellitus Treated in Peru Medical Center - José Ander Asenjo Alarcón (Revista Finlay)
Background: type 2 diabetes mellitus is a very frequent chronic disease. Its characteristics and associated comorbidities are well known, however, the response of patients to conventional treatments is not always effective. It is necessary to increase the patients’ particular characteristics knowledge to achieve individualized management. Objective: to describe the sociodemographic and pathological characteristics of patients with type 2 diabetes mellitus treated in Chota medical center, Peru. Methods: a descriptive, cross-sectional and retrospective study was carried out in 102 patients treated at the Chota medical health center in Peru, carried out during February and March 2015. Sociodemographic and pathological characteristics were the variables analyzed and were identified in a medical record data collection. Absolute and relative frequencies, measures of central tendency, dispersion and confidence intervals for proportions at 95 % were described. Results: 81.4 % of the patients were married, worked as teachers in activity or unemployed (52.0 %), with an average age of 59 years old (58.9 % of men ≥60 years and 56.5 % of women between 30 and 59 years old), in treatment with glibenclamide + metformin (55.8 %) and diet + exercise (75.5 %), with an illness average time of 6.6 years (56.6 % of women and 41.1 % of males ≤ 5 years). Conclusion: the majority of patients with DM2 were married, teachers, with an average age of 59 years old, on treatment with glibenclamide + metformin and diet + exercise, they suffer from the disease for an average of 6.6 years.